RETRACTED: Technique for estimating the time spent on measuring and computing process in three-dimensional electrical impedance tomography - Aleksanyan Grayr; Kucher Artem; Shcherbakov Ivan (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001